Virtual Conventional Therapy for Motor Rehabilitation in Stroke Patients: A Systematic Review - Rudi Ilhamsyah; Yetty Hambarsari; Markus Santoso; Hendry Gunawan; Esti Nur Ekasari; Krisandi Hartanto; Han Yang (Magna Neurologica, 2025)
Background: Stroke is a leading cause of disability worldwide, significantly impacting motor function, sensory, visual, and cognitive abilities. Conventional physical therapy has traditionally been used for stroke rehabilitation. However, technological advances have introduced virtual reality (VR) as a rehabilitation tool. Research has highlighted the therapeutic value of VR in improving motor functions, with some studies suggesting superior outcomes compared to traditional therapy. Despite this, the literature presents varied results, necessitating a systematic review to evaluate the breadth of evidence. Objective: This study aims to compare the effectiveness of VR therapy with conventional physical therapy in extremity function among stroke patients. Methods: A primary search was conducted across PubMed, Scopus, and ProQuest databases using keywords related to stroke, VR, and conventional therapy. Studies will be included if they compare the efficacy of VR with conventional therapy in stroke rehabilitation. Non-comparative studies, non-English publications, and irrelevant topics will be excluded. Results: A literature search yielded 15 eligible journals using a randomized clinical trial. Analysis showed that 4 out of 15 articles found VR therapy not superior to conventional therapy, while the other 11 articles demonstrated that VR therapy statistically improved patient conditions compared to conventional therapy. Conclusion: VR-based exercises stimulate cortical reorganization and strengthen neural systems involved in motor planning, learning, and execution. Most studies indicate that VR therapy is more effective in enhancing motor recovery, balance, and limb function in stroke patients and increasing patient motivation and engagement than conventional training.